My philosophical credo - Bańka, Józef (Folia Philosophica, 2005)
In this article the author made an attempt to define recentivism from the perspective of the quantum comprehension of time. In other words, he tackles the issues connected with a time quantum treated as a point „now” (Lat. recens). The author illustrates the problem through the holographic rule, according to which a quantum state of a certain area of space-time can be encoded on the edge of this area. It turns out that the holographic rule, understood in this way, can be included in a whole, in which locans of an event can be encoded in a central part of a quantum state of a certain space-time area, whereas a phenomenon - that is, the part of the event known to the experiencing subject - can be encoded on the edge of this area. It means that any event that happens now, creates a phenomenon, which, as a quantum state of space-time, can be encoded on the edge of the event, in the way that the first part of the phenomenon is located in the anterior time (recens quo ante) and the second one in the posterior time (recens ad quern). On such a basis, the author defines recentivism as the idea, according to which the world is born anew with every experience (a recentiori), although it once existed in a certain form.